A rare case of May-Thurner syndrome due to external compression of the right and left common iliac veins - Logan Schwarzman, MD; Jack Aguilar, MD; Nichelle Megowan, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
May-Thurner syndrome, also known as external iliac compression syndrome, is a rare but commonly underdiagnosed cause of asymmetric lower extremity edema. Here we describe a case of May-Thurner syndrome owing to external compression of the right and left common iliac veins presenting as chronic worsening asymmetric right greater than left lower extremity edema. Initial etiology workup was unremarkable, and further diagnostics revealed compression of the right common iliac vein at the bifurcation of the right common iliac artery between the right external and internal iliac arteries with concomitant compression of the left common iliac vein. Stenting of the right common iliac vein was completed, with significant symptomatic improvement at 30-day follow-up. This case documents a unique variant of May-Thurner syndrome rarely described in the literature.